Profil Aspek Sosial, Aspek Ekonomi, dan Aspek Teknis Subak Lepang Pesedahan Toya Jinah Desa Takmung, Kecamatan Banjarangkan, Kabupaten Klungkung - PUTU WIRAADI KUSUMA; DEWA PUTU OKA SUARDI; NI WAYAN SRI ASTITI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Subak Lepang is located in Banjarangkan District, Klungkung Regency with an area of 165 hectares. That subak is experiencing water limitations so that the farmers are very difficult toget water. Besides that, the dry season is too long, at night the subak members must close thetertiary channel in order to get higher water volume into the rice field. Based on the casehence purpose of this study to know profile of Subak Lepang viewed from social aspect,economic aspect and technical aspect. This research data obtained through structuredinterviews and documentation then it analyzed by using descriptive qualitative analysismethod. The result of this study shows that profile of Subak Lepang viewed from economicaspect is included in high category (69,78%) and from technical aspect included in highcategory (70,21%) and social aspect included in medium category (67,07%). On theeconomic aspect, this is due to the cooperation between subak and cooperatives regarding thedistribution of subak fertilizer. Technical aspects shows that the maintenance of irrigationfacilities obtain a high indicator because subak members able to maintain and keep the SubakLepang’s irrigation facility. Social aspect in moderate category due to rare water so thatsubak members should able to manage water more efficient. Therefore, subak membersshould together to provide a water reservoir for used irrigation so that during the dry seasonthey not lack of water in the rice field.